The effectiveness of corporatization from Bank Pertanian Malaysia to Agrobank / Nurain Izyani Kahpi - Kahpi, Nurain Izyani (Faculty of Business and Management, 2010)
This study focuses on “The effectiveness of corporatization from Bank Pertanian Malaysia to Agrobank” and the objective is to determine the level of effectiveness of Agrobank Corporatization, to identify factors influence the effectiveness of Agrobank corporatization and to provide suggestion to recommend to increase the effectiveness of Agrobank corporatization. The development of corporatization in Malaysia is a new scenario to the Government Company and also public sector that rebrand their company into the new face such as company policy, logo, product and services and also their goals and objective. For Agrobank corporatization, there are four factors that contributing to their corporatization effectiveness, which are staff attitude, technology and system, marketing strategies and customer service. In getting the data information needed, the primary data was obtained from the survey method. It was more on quantitative research, where survey instrument in which questionnaire have been used in this study. It involved a structured questionnaire given to the respondents to elicit the information. The sample for this study was the customer of Agrobank Sekinchan branch and 60 sets of questionnaires have been distributed personally to the respondents. Overall, this study has come up with a new research model through the relevant of the previous study.